Postmodernisme dan Filsafat Pendidikan Islam - Mukalam (Jurnal Pendidikan Islam, 2013)
Philosophy of Islamic education is a field of study that has not been touched very much by the idea of postmodernism. When it is interpreted and constructed, the project of postmodernism is a critical metanarrative, the critic of knowledge objectivity, and the critic of autonomy subject, which provides insight and new perspectives for the study of Islamic philosophy. Philosophy of Islamic education is developed to appreciate the small narrative and local knowledge; examine the relation of knowledge and power, and posture the subject instability.